2022
DOI: 10.55630/sjc.2021.15.85-128
|View full text |Cite
|
Sign up to set email alerts
|

Before We Can Find a Model, We Must Forget about Perfection

Abstract: With Reinforcement Learning we assume that a model of the world does exist. We assume furthermore that the model in question is perfect (i.e. it describes the world completely and unambiguously). This article will demonstrate that it does not make sense to search for the perfect model because this model is too complicated and practically impossible to find. We will show that we should abandon the pursuit of perfection and pursue Event-Driven (ED) models instead. These models are generalization of Markov Decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…All we need is a sufficiently good model which works for us. In [8] we explained why trying to find a perfect model of the world is an overly ambitious goal. Nevertheless, we will assume that a perfect model of the world does exist and that model provides the definition of the world.…”
Section: 2mentioning
confidence: 99%
“…All we need is a sufficiently good model which works for us. In [8] we explained why trying to find a perfect model of the world is an overly ambitious goal. Nevertheless, we will assume that a perfect model of the world does exist and that model provides the definition of the world.…”
Section: 2mentioning
confidence: 99%
“…The agent can influence even those events which are not driven by her actions. This is described in [9]. For these events the agent may have some "preference" and by her "preferences" the agent could have some influence on whether an event will or will not occur.…”
Section: 6mentioning
confidence: 99%
“…For most authors, non-deterministic implies that for each possible event there is one precisely defined probability. In [8,9] we showed that the latter statement is too deterministic. Telling the exact probability of occurrence for each and every event would be an exaggerated requirement.…”
Section: 1mentioning
confidence: 99%